Social self-efficacy sebagai mediator dampak pola asuh autoritatif dan social-emotional skills pada perilaku prososial remaja: Social self-efficacy as a mediator of the impact of authoritative parenting style and social-emotional skills on adolescent prosocial behavior - Winahyu, Dyah Mustika Kusuma; Farozin, Muh (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
The purpose of this study was to determine whether or not there is a direct and indirect influence between social-emotional skills, authoritative parenting, and social self-efficacy on the prosocial behavior of high school students in the Sidoarjo Regency. This type of research uses an ex post facto quantitative research model using a survey in Sidoarjo Regency. The sampling technique used a multistage with a total of 375 respondents. The data collection method used a modification of the Adolescent social self-efficacy scale (α = 0.760), Parenting style scale (α = 0.720), Social-emotional learning competencies scale (α = 0.793), and Prosocial Tendencies Measurements (α = 0.734). The data were analyzed using a path analysis model using IBM SPSS 25 and the Sobel online calculator to validate the significance of the indirect effect. The results of this study found that both social-emotional skills, authoritative parenting, and social self-efficacy have a positive and partially significant direct influence on prosocial behavior. Furthermore, social-emotional skills and authoritative parenting are known to have an indirect influence through social self-efficacy as a mediator on the prosocial behavior of adolescent students. There is a positive and significant direct influence between authoritative parenting and social-emotional skills on prosocial behavior, and there is a significant indirect influence through social self-efficacy as a mediator variable of authoritative parenting and social-emotional skills on adolescent prosocial behavior.